STUDI KASUS PERILAKU TEMPER TANTRUM ANAK DALAM BERSOSIALISASI DI TK DHARMA WANITA KEMPLENG II - Siti Fatimah; Tomas Iriyanto; Nur Anisa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Tantrum tempering is a common behavioral problem experienced by preschoolers by expressing anger by sleeping on the floor, thrashing, screaming. Tantrum temperatures usually occur in children who are active and have abundant energy. This arises because at the age of 4-5 years children are still easily provoked by emotions that can be caused by not fulfilling the physical needs of children in terms of eating patterns and resting children. Factors causing children to experience temper tantrum is actually one form of emotional development of children that cannot be controlled. Based on preliminary observations of case studies that have been conducted by researchers found that there is one child who has a unique behavior on Dharma Wanita Kempleng II Kindergarten, Kediri Regency with the initials AFN. AFN is a 5-year-old child who studies in kindergarten group A. AFN tends to be angry, does not care when reprimanded by people around AFN, and shows a cool face towards friends. The behavior exhibited from AFN is quite common when at school or at home. AFN when he feels he does not like what others do to him and feels not according to expectations AFN will show a cool face, hit, say rude, the child sometimes even laughs when he sees his friend crying, if AFN's desire is not fulfilled AFN will scream and ruffle things those around it will cry. At this exposure if a child who has not been able to control his emotions will automatically inhibit the child's emotional social development. This can have an impact on social skills. Socialization in learning in PAUD is an interaction that occurs between children, parents or adults, and educators in a particular environment. Based on the results of the reduction carried out by researchers. Children who experience temper tantrums experience some obstacles in socializing because children can behave aggressively to friends or others who make it become shunned by friends for fear of the child hurting friends or others around him.